The Relationship Between Tourism Accessibility and Tourist Satisfaction - Raffi Auliya Ramadhan; Rifqi Asy'ari; Irena Novarlia (Jurnal Pariwisata Nusantara (JUWITA), 2026)
Purpose: This study aims to examine the relationship between tourism accessibility and tourist satisfaction, and the influence of tourism accessibility on tourist satisfaction at Toga Hill Sumedang. Method: A quantitative approach with descriptive and verification analysis was employed. Data were collected from April to May 2026 through onsite and online questionnaire distributed to visitors of Toga Hill Sumedang. A total of 400 usable respondent questionnaire were obtained using an accidental sampling technique. Data were analyzed using descriptive statistics, classical assumption tests, simple linear regression, the coefficient of determination, and t-tests using IBM SPSS Statistics. Because accidental sampling is a non-probability sampling technique, the findings should be interpreted within the characteristics of the surveyed respondents and should not be generalized to the entire visitor population. Result: The mean accessibility score was 12.53 (possible score range: 5–20), while the mean tourist satisfaction score was 12.59 (possible score range: 5–20). Simple linear regression analysis indicated a statistically significant positive association between perceived tourism accessibility and tourist satisfaction (t = 9.543, p < .001). The coefficient of determination (R² = .186) indicates that accessibility accounted for 18.6% of the variance explained by the present model. Contribution: This study provides empirical evidence regarding the relationship between tourism accessibility and tourist satisfaction at a hill-based nature tourism destination. The findings offer practical insights for destination managers and local governments to improve road accessibility, transportation convenience, route information, and travel comfort to enhance visitors’ overall travel experience.